Eco-Morphological and Physiological Behaviours of Atriplex halimus L. Under Different Natural Habitats - Ola Abd Elbar; Mona Abd Elhalim; Mohamed Abd El-Maboud; Karam Mostafa (Arab Universities Journal of Agricultural Sciences)
Atriplex halimus is a widely distributed species in the Mediterranean coastal areas and can grow under saline and non-saline habitats. Plant leaves were collected from two habitats; non-saline (1.14 dSm-1) and saline (30.63 dSm-1) at Borg Alarab area along the Northwestern coast of Egypt to investigate the ecomorphological and physiological behavior variations of A. halimus in relation to different habitat. leaf area, specific leaf area (SLA), water content, chl a, chl b, total chl, carotenoids, Na+, K+, Ca++ and Cl- contents were measured. A. halimus leaves generate adaptive changes as plastic responses to salinity by the decrease in leaf area, SLA, chl a, chl b, totat chl and Cl and increase in Na+ , phenylalanine ammonia lyase (PAL) specific activity and total phenols content.